Russian experience with injectable chondroitin sulfate and glucosamine sulfate: a review of clinical trials - A. E. Karateev (Современная ревматология, 2018)
The widespread use of parenteral chondroprotectors is a feature of Russian medical practice. There are many drugs of this series in a Russian physician's arsenal, including chondroitin sulfate (CS),  glucosamine sulfate (GS), glycosaminoglycan-peptide complex, and  bioactive concentrate from small sea fish for intramuscular  injections. The paper analyzes Russian trials of the efficacy and  safety of two injectable formulations of CS and GS (ICS and IGS).  ICS was tested in 17 articles containing a total of 1639 patients with  osteoarthritis (OA), non-specific back pain (NBP), or shoulder  fractures and pain after stroke. Standard therapy (NSAIDs +  physiotherapy) served as a control in the majority of the paper. In  these trials, the reductions in visual analog scale (VAS) and WOMAC pain in OA treated with ICS averaged 58.2±22.3% and those were 26.1±14.7% in the control groups; the reductions in VAS NBP  reached an average of 87.1±16.8 and 62.2±21.7%, respectively.  ICS also showed a good effect in shoulder fractures and pain after a  stroke. The number of local adverse reactions after injections was  insignificant (4.4%); they did not threaten the health of patients and they caused ICS to be discontinued only in 3 cases. IGS was  investigated in two trials (n=154), which confirmed its efficacy (total pain relief >50%) and relative safety. Thus, the data of Russian trials suggest that ICS and IGS have good therapeutic potential and favorable tolerance.